Relations among Temperament, Self-regulatory Strategies and Gender in Predicting Delay of Gratification - Hong, Fang; Doan, Stacey N.; Lopez, Angelica; Evans, Gary W. (Frontiers in Psychology, 2017)
Self-regulation is associated with many positive outcomes, but there is limited information about individual difference regarding children’s spontaneous use of strategies to self-regulate and the relative success of those strategies. In the current study, we examined whether temperament and gender are associated with self-regulation and explored the types of spontaneous strategies children use during Mischel’s delay of gratification protocol. In addition, we investigated whether spontaneous strategy use during the task could moderate the effects of temperament on self-regulation and whether temperament would mediate the effect of gender on self-regulation. Participants were 349 9-year-olds (182 boys, Mage = 9.18, SD = 1.17). Mothers reported on children’s temperament and the Delay of Gratification task was used to assess self-regulation. Both temperament and child’s gender were significantly associated with children’s delay time. Girls were able to delay longer than boys, and children scoring high on activity level were less able to delay. Activity level also mediated the relationship between gender and delay time. Finally, we found an interaction effect between activity level and certain strategies in relation to self-regulatory behavior.